Flexible anti-static high-temperature-resistant FDC special film and preparation method thereof

The FDC special film integrates modified Ti3C2Tx nanosheets and graphene to create a flexible, anti-static, and thermally stable composite film, overcoming the performance gaps in existing materials for high-temperature applications.

CN120310258AActive Publication Date: 2025-07-15HUNAN YISIDI TECH CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202510525293.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-07-15
Estimated Expiration
2045-04-25

AI Technical Summary

Technical Problem

Existing FDC special films lack simultaneous performance in flexibility, anti-static properties, and high-temperature resistance, leading to issues such as thermal degradation, poor electrical conductivity, and mechanical instability in harsh environments.

Method used

A flexible anti-static high-temperature FDC special film is developed using a composite structure of modified Ti3C2Tx nanosheets and graphene-based polyimide, enhanced by a multi-component formulation and controlled thermal processing, ensuring uniform dispersion and stable electrical conductivity.

Benefits of technology

The film achieves enhanced flexibility, persistent anti-static performance, and thermal stability, addressing the limitations of existing materials in extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120310258A_ABST
    Figure CN120310258A_ABST
Patent Text Reader

Abstract

The invention relates to the field of FDC special film materials, and provides a flexible anti-static high-temperature-resistant FDC special film and a preparation method thereof.The flexible anti-static high-temperature-resistant FDC special film is prepared from a polyimide / graphene precursor solution, a surface modified Ti3C2Tx nanobelt, 3-aminopropyltriethoxysilane, 2, 3, 4-trimethyl-1, 3-pentanediol monoisobutyrate, 2, 3-pentanediol monoisobutyrate and a graphene oxide precursor solution. The composition is composed of 2, 2 '-dihydroxy diphenyl ether, 1-ethyl-3-methylimidazole bis (trifluoromethanesulfonyl) imide salt and diisononyl phthalate. The Ti < 3 > C < 2 > T < x > nanobelt is subjected to ionic liquid surface modification, so that the dispersity and interfacial compatibility of the Ti < 3 > C < 2 > T < x > nanobelt in a polyimide matrix are enhanced. The composite film with excellent flexibility, stable conductivity and high thermal stability is prepared through multi-step compounding, functionalization treatment and a hot-pressing curing process. The film is suitable for flexible electronics, heat-resistant insulating materials and high-temperature anti-static scenes, and has wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of FDC special film materials, and particularly to a flexible antistatic and high-temperature resistant FDC special film and a preparation method thereof. Background Art

[0002] In frontier fields such as aerospace, flexible displays, smart wearable devices, and high-frequency communication electronics, flexible functional materials are becoming one of the key supporting technologies. Especially for flexible electronic devices operating in high-temperature, high-electric-field, or strong-friction environments, more stringent multiple performance requirements are imposed on their constituent materials. On the one hand, the materials need to have excellent flexibility and mechanical toughness to adapt to complex curved surfaces, dynamic deformations, or repeated folding usage conditions; on the other hand, the materials also need to have stable and durable conductive properties to achieve electrostatic dissipation, signal transmission, or electromagnetic shielding functions, avoiding the risk of device failure caused by electrostatic accumulation; in addition, in high-temperature environments, the materials need to maintain structural integrity and electrical performance stability, with excellent thermal stability and heat decomposition resistance, to ensure the long-term reliable operation of the devices. Therefore, developing high-performance film materials with flexibility, antistatic, and high-temperature resistant properties can not only effectively improve the reliability, safety, and service life of terminal devices, but also promote industries such as flexible electronics, precision instruments, and high-end manufacturing towards higher-performance and wider-adaptability application systems, having important engineering value and industrial prospects.

[0003] Although significant progress has been made in recent years in the directions of flexible materials, antistatic coatings, and high-temperature resistant polymers, there are still obvious shortcomings in the existing material systems in simultaneously meeting the three properties of flexibility, antistatic, and high-temperature resistance. For example, the Chinese patent with the publication number CN105085956B discloses a preparation method of an antistatic polyimide shielding black film, which has good flexibility and initial conductivity, but its conduction path is prone to thermal degradation and failure in high-temperature environments, lacking thermal stability guarantee; another example is CN101827882B, which discloses a polyimide film with excellent thermal stability, having strong thermal stability, but due to the too high rigidity of the inorganic filler, the overall flexibility of the film material is insufficient, making it difficult to meet the deformation usage requirements of flexible electronics. In addition, currently, a large number of antistatic film products use metal coatings or carbon-based fillers to construct a conductive network, but their dispersibility is poor and the interfacial compatibility is low, and it is extremely easy to cause the interruption of the conductive channel under heat treatment or stress, resulting in problems such as large resistance fluctuations and unstable electrostatic dissipation performance. The fundamental reason for these problems is the lack of multi-scale collaborative design in the material system, and the organic unity of flexible mechanical properties, conductive functions, and thermal stability has not been achieved at the molecular structure, interface regulation, and composite construction levels. Therefore, there is an urgent need to develop a new material system with breakthroughs in microstructural regulation, molecular-level composite, and processing technology collaborative optimization to achieve the synergistic improvement of the three properties and meet the high-performance requirements in complex application environments. Summary of the Invention

[0004] (1) Technical problem to be solved

[0005] The object of the present invention is to provide a flexible anti-static and high-temperature resistant FDC special film and its preparation method, so as to solve the problems of insufficient flexibility, anti-static property and high-temperature resistance of the current FDC special film.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solution:

[0008] A flexible anti-static and high-temperature resistant FDC special film, comprising the following raw materials in parts by weight: 70 - 85 parts of polyimide / graphene precursor solution, 3.0 - 7.0 parts of surface-modified Ti3C2T x nanoribbons, 0.5 - 1.0 part of 3-aminopropyltriethoxysilane, 0.5 - 1.5 parts of 2,2'-dihydroxydiphenyl ether, 0.5 - 1.5 parts of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and 1.0 - 3.0 parts of diisononyl phthalate.

[0009] The surface-modified Ti3C2T x nanoribbons are obtained by surface modification of Ti3C2T x nanoribbons with 1-butyl-3-methylimidazolium tetrafluoroborate;

[0010] Furthermore, the preparation method of the polyimide / graphene precursor solution is as follows: Add 2.5 - 4.5 parts of reduced graphene oxide to 3 - 8 parts of N-methylpyrrolidone, and disperse it by ultrasonic for 30 - 45 min to fully disperse the reduced graphene oxide sheets at the molecular scale to form a uniform and stable graphene dispersion; Add 9.0 - 11.0 parts of 4,4'-diaminodiphenyl ether to the above graphene dispersion, stir and dissolve it under nitrogen protection at a stirring rate of 300 - 400 rpm, and then cool the system to 0 - 5°C; Slowly add 13.0 - 15.0 parts of 4,4'-diphenylether dianhydride to the above low-temperature solution in batches. During the reaction, continuous nitrogen protection is maintained, the stirring rate is kept at 300 - 400 rpm, the temperature of the reaction system is controlled at 0 - 5°C, and the stepwise addition time is controlled at 2.5 - 3.5 h. After the dianhydride is completely dissolved, continue to react at a constant stirring rate for 5 - 7 h to obtain a polyamic acid precursor solution containing graphene, that is, a polyimide / graphene precursor solution.

[0011] Further, the method for preparing the reduced graphene oxide is as follows: Disperse 9.0 - 12.0 parts of graphene oxide in 80.0 - 100.0 parts of deionized water, stir at a stirring rate of 400 - 600 rpm for 30 - 45 min. After forming a uniform dispersion, slowly add 2.0 - 4.0 parts of vitamin C reducing agent, control the pH value of the system between 4.0 and 6.0, and then heat and react at 80 - 95 °C for 90 - 120 min. Continuously stir during the reaction process to make the reduction reaction proceed uniformly. After the reaction is completed, cool the obtained mixed solution to room temperature, centrifuge at 8000 - 10000 rpm for 10 - 15 min to collect the precipitate, discard the supernatant, and wash it repeatedly with deionized water 3 - 5 times, with the amount of each washing solution being 80 - 120 mL until the pH value of the washing solution is stable between 6.5 and 7.5. Dry the obtained precipitate under a vacuum condition of 0.05 - 0.08 MPa for 18 - 24 h to obtain the reduced graphene oxide.

[0012] The design of the polyimide / graphene precursor solution in the present invention is mainly used to enhance the comprehensive performance of the flexible anti-static and high-temperature resistant special film. This design introduces reduced graphene oxide into the polyamic acid system to construct a uniform and stable composite structure at the molecular scale, thereby achieving the synergistic improvement of mechanical flexibility, electrical properties, and thermal stability. During the preparation process, first, N-methylpyrrolidone is used as the dispersion medium, and ultrasonic dispersion is used to fully exfoliate and uniformly distribute the reduced graphene oxide sheets to ensure their effective participation and interfacial bonding in the subsequent polymerization reaction. Subsequently, under nitrogen protection, 4,4'-diaminodiphenyl ether and 4,4'-diphenyl ether dianhydride are introduced in sequence under specific temperature and time conditions to form the polyamic acid main chain, and form good physical cross-linking and interfacial interactions with the graphene sheets, thereby constructing a composite precursor solution with a continuous phase structure. In this system, the reduced graphene oxide effectively improves the anti-static ability of the material through its high specific surface area and excellent electron conduction performance. At the same time, its two-dimensional sheet structure also endows the composite system with good flexibility and thermal stability. The polyamic acid precursor can be transformed into a polyimide skeleton during the subsequent heat treatment process, providing excellent high-temperature resistance and mechanical strength. It should be noted that the reduced graphene oxide used here is obtained by the mild reduction of graphene oxide with vitamin C. This method not only ensures the integrity and dispersion of the graphene sheets but also avoids the structural damage and impurity introduction caused by strong reducing agents, thereby further improving the stability and reliability of the system. Through the synergistic effect of the above components, the present invention realizes the organic integration of high flexibility, high conductivity, and high thermal stability functions, providing a practical and process-controllable technical route for the preparation of flexible functional films with multi-performance integration.

[0013] Further, the surface-modified Ti3C2T x The preparation method of the nanoribbon is as follows: Mix 1.0 - 1.5 parts of Ti3C2Tx The nanobelts are mixed with 2.0 - 3.0 parts of 1-butyl-3-methylimidazolium tetrafluoroborate in proportion and ball-milled in a planetary ball mill for 60 - 70 min. The obtained solid is added to 100 - 120 parts of a mixed solution of deionized water and absolute ethanol with a volume ratio of 2:1, and ultrasonically treated for 55 - 65 min under the condition of an ultrasonic power of 200 - 300 W. After treatment, it is centrifuged at 12000 - 15000 rpm for 15 - 20 min, the supernatant is discarded and the precipitate is retained. The obtained precipitate is washed alternately with water and ethanol 3 - 4 times and then freeze-dried at -40 - -50 °C for 18 - 24 h, and finally surface-modified Ti3C2T x nanobelts are obtained.

[0014] Furthermore, the preparation method of the Ti3C2T x nanobelts is as follows: First, 10.0 - 15.0 parts of Ti3AlC2 powder are slowly added to 100.0 parts of a hydrofluoric acid (HF) solution with a mass concentration of 35% - 45%, and magnetically stirred at a rate of 200 - 300 rpm at 40 - 45 °C for 22 - 26 h to achieve selective etching of the Al layer in Ti3AlC2 to generate a Ti3C2T x precursor solution. After the reaction is completed, the mixture is centrifuged at 5000 - 6000 rpm for 10 - 15 min, the supernatant is discarded and the precipitate is retained, and it is washed 4 - 6 times with deionized water, with the amount of each washing solution being 80 - 120 mL, until the pH value of the washing solution is stabilized between 6.5 - 7.5. The obtained Ti3C2T x wet precipitate is freeze-dried for 18 - 24 h to obtain Ti3C2T x powder. Subsequently, 2.0 - 3.0 parts of Ti3C2T x powder is dispersed in 100.0 parts of a potassium hydroxide (KOH) solution with a mass concentration of 5.5 - 6.5 mol / L, and continuously stirred and reacted at 25 - 30 °C under nitrogen protection for 20 - 30 h, with the stirring rate controlled at 250 - 350 rpm. During the reaction process, the Ti3C2T x lamellae are gradually sheared and peeled along the interlayer direction in the alkaline solution to form a one-dimensional ribbon structure. After the reaction is completed, the system is centrifuged at 5000 - 6000 rpm for 10 - 15 min, the supernatant is discarded, the precipitate is retained and washed with deionized water until the pH value is restored to 6.5 - 7.5. Finally, the obtained precipitate is dried under a vacuum condition of 0.05 - 0.08 MPa for 20 - 24 h to obtain Ti3C2T x nanobelt powder.

[0015] Furthermore, the average width of the Ti3C2T x nanobelts is 50 - 150 nm; the average length is 1.5 - 3.5 μm;

[0016] Further, the Ti3C2T x is a two-dimensional carbide with surface terminal groups selected from fluorine (F), hydroxyl (OH), and oxygen (O).

[0017] The present invention uses surface-modified Ti3C2T x nanoribbons, and the design is mainly used to enhance the electrical conductivity, thermal stability, and interfacial synergy performance of flexible anti-static and high-temperature-resistant special films. This technical solution realizes the uniform dispersion of Ti3C2T x nanoribbons in the polymer matrix and the significant improvement of their functional synergy performance through the structural regulation and surface modification of Ti3C2T x nanoribbons. First, the preparation of Ti3C2T x nanoribbons uses Ti3AlC2 as a precursor, and selective etching is carried out with a high-concentration hydrofluoric acid solution under controlled temperature and stirring rate conditions to effectively remove the Al layer and generate a lamellar Ti3C2T x structure. After multiple washings and freeze-drying, a high-purity two-dimensional carbide material is obtained; subsequently, it is dispersed in a potassium hydroxide solution for long-term alkaline shear peeling, so that the Ti3C2T x lamellae are transformed into one-dimensional ribbon structures with a high aspect ratio along the interlayer direction, significantly improving their distribution stability and network construction ability in the composite material; on this basis, 1-butyl-3-methylimidazolium tetrafluoroborate is used to perform surface functionalization modification on the obtained nanoribbons, and the ball milling and ultrasonic combination method is used to enhance the interaction between the ionic liquid and the Ti3C2T x surface, so that the surface terminal groups can be regulated to form a coating layer with excellent interfacial activity, thereby improving the dispersibility of the nanoribbons in polar or weakly polar systems and the interfacial binding ability with the polymer matrix. The finally obtained surface-modified Ti3C2T

[0018] The present invention also discloses a preparation method for a flexible anti-static and high-temperature-resistant FDC special film, including the following steps:

[0019] S1. Mix the polyimide / graphene precursor solution with the surface-modified Ti3C2T x nanoribbons to form a dispersion under mechanical stirring;

[0020] S2. Heat the dispersion and dropwise add 3-aminopropyltriethoxysilane for functionalization treatment;

[0021] S3. Add 2,2'-dihydroxydiphenyl ether, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and diisononyl phthalate and carry out constant-temperature blending;

[0022] S4. Filter, defoam, and then coat to form a film;

[0023] S5. Gradually increase the temperature for hot pressing and curing, and then cool to obtain the finished product.

[0024] Furthermore, the entire process of steps S1 to S5 is carried out under a nitrogen protection atmosphere;

[0025] In step S1, the stirring rate is 500 - 700 rpm, the stirring time is 40 - 60 min, and the ambient temperature is 25 - 30 °C;

[0026] In step S2, the mixed solution is heated to 80 - 90 °C, the dropping rate of 3-aminopropyltriethoxysilane is 0.1 - 0.3 mL / min, the stirring rate is 400 - 600 rpm, the reaction time is 60 - 90 min, and the reaction is carried out under nitrogen protection;

[0027] Furthermore, in step S3, the constant-temperature stirring temperature is 80 - 90 °C, and the time is 30 - 45 min;

[0028] In step S4, the precursor solution is filtered through a 0.45 μm polytetrafluoroethylene filter membrane, the vacuum defoaming pressure is -0.08 to -0.1 MPa, the defoaming time is 20 - 30 min, the coating thickness is 50 - 80 μm, the film scraping rate is 3 - 5 mm / s, the pre-drying temperature is 80 - 100 °C, and the time is 30 - 60 min;

[0029] Furthermore, in step S5, the hot pressing heating rate is 3 - 5 °C / min, the heat treatment temperature is 250 - 300 °C, the heat preservation time is 1.5 - 2.5 h, the cooling rate is 1 - 2 °C / min, and the whole process is carried out under a nitrogen atmosphere.

[0030] The design of the present invention, which combines multi-component synergistic construction and gradient hot pressing and curing, is mainly used to enhance the structural integrity, conductive stability, and thermal environment adaptability of the flexible antistatic high-temperature-resistant FDC special film. This technical solution ensures the effective dispersion, interfacial reaction, and synergistic effect of each functional component in the composite system by scientifically arranging the process parameters and the introduction order of the components, thereby endowing the final film material with multiple performance advantages. In the initial step, the polyimide / graphene precursor solution and surface-modified Ti3C2T x nanoribbons are fully mixed at an appropriate temperature and stirring rate, effectively ensuring the combination of graphene and Ti3C2T xThe uniform distribution at the molecular level provides a high-quality dispersion basis for subsequent functional construction; subsequently, 3-aminopropyltriethoxysilane is added dropwise under heating conditions for functional group introduction, and its surface reaction improves the inorganic / organic interface compatibility and forms stable chemical bonding at the interface, enhancing the structural stability and interface energy transfer ability; on this basis, 2,2'-dihydroxydiphenyl ether is further introduced as a heat stabilizer, synergistically with the ionic lubrication and conductive functions of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and the flexible regulation effect of diisononyl phthalate, to form a uniform composite system under isothermal blending conditions, improving the overall flexibility and thermal decomposition resistance; after completing the component construction, filtration and defoaming are carried out to ensure that the film material has no bubble defects, and then under nitrogen protection, a gradient heating and hot pressing curing process is used to convert polyamic acid into polyimide while stably constructing the network structure between components, finally forming a composite film with a dense structure, stable conductive channels and excellent heat resistance. The nitrogen protection environment during the entire preparation process effectively avoids oxidation and degradation at high temperatures, ensuring the performance stability of the film material, and the precise control of the parameters in the film scraping, hot pressing and cooling processes further improves the film forming quality and thickness uniformity. The components achieve synergistic effects at multiple levels such as physical dispersion, chemical reaction and interface regulation, making the finally obtained FDC special film have good flexibility, persistent antistatic ability and excellent thermal stability, meeting the multiple requirements in fields such as flexible electronics, thermal protection and high-end packaging under harsh environments.

[0031] (3) Beneficial technical effects

[0032] 1. By introducing vitamin C-reduced graphene oxide into the polyamic acid system, the present invention constructs a uniform composite structure, realizes the synergistic improvement of flexibility, antistatic and high-temperature resistance performance, solves the problems of unstable conductivity and easy thermal decomposition of existing film materials, and is applicable to fields such as high-temperature flexible electronics.

[0033] 2. By surface-modifying Ti3C2T x nanoribbons to construct a stable conductive network, the present invention solves the problems of poor conductivity and low thermal stability of existing film materials. The core components synergistically improve the interface combination and dispersibility, significantly enhancing the comprehensive performance of the film material, and are applicable to fields such as high-temperature flexible electronics.

[0034] 3. Through multi-component synergy and gradient hot pressing curing, the present invention realizes the dense structure of the film material, stable conductive channels and optimized interface compatibility, significantly improving the flexibility, antistatic and high-temperature resistance performance, solving the problems of fast thermal decomposition and unstable conductivity in the prior art, and is applicable to the field of high-end flexible electronics. Description of the drawings

[0035] Figure 1 is the morphology diagram of the Ti3C2T x nanoribbons prepared in Example 1 of the present invention.

[0036] Figure 2 Ti3C2T prepared in Example 1 of the present invention x XRD phase analysis diagram of the nanoribbon. Specific implementation mode

[0037] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.

[0038] Example 1

[0039] A flexible anti-static and high-temperature-resistant FDC special film, comprising the following raw materials in parts by weight: 70 parts of polyimide / graphene precursor solution, surface-modified Ti3C2T x 3.0 parts of nanoribbons, 0.5 part of 3-aminopropyltriethoxysilane, 0.5 part of 2,2'-dihydroxydiphenyl ether, 0.5 part of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and 1.0 part of diisononyl phthalate.

[0040] The surface-modified Ti3C2T x The nanoribbons are Ti3C2T x The nanoribbons are obtained by surface modification with 1-butyl-3-methylimidazolium tetrafluoroborate;

[0041] The preparation method of the polyimide / graphene precursor solution in this example is as follows: Add 2.5 parts of reduced graphene oxide to 3 parts of N-methylpyrrolidone, and disperse it by ultrasonic for 30 min to fully disperse the reduced graphene oxide sheets at the molecular scale to form a uniform and stable graphene dispersion; Add 9.0 parts of 4,4'-diaminodiphenyl ether to the above graphene dispersion, dissolve it under nitrogen protection and at a stirring rate of 300 rpm, and then cool the system to 0 °C; Slowly add 13.0 parts of 4,4'-diphenylether dianhydride to the above low-temperature solution in batches. During the reaction, nitrogen protection is continuously maintained, the stirring rate is maintained at 300 rpm, the temperature of the reaction system is controlled at 0 °C, and the gradual addition time is controlled at 2.5 h. After the dianhydride is completely dissolved, continue to react at a constant stirring rate for 5 h to obtain a polyamic acid precursor solution containing graphene, that is, a polyimide / graphene precursor solution.

[0042] The preparation method of reduced graphene oxide in this example is as follows: Disperse 9.0 parts of graphene oxide in 80.0 parts of deionized water, stir at a stirring rate of 400 rpm for 30 min. After forming a homogeneous dispersion, slowly add 2.0 parts of vitamin C reducing agent, control the pH value of the system between 4.0, and then heat and react at 80 °C for 90 min. During the reaction process, continuously stir to make the reduction reaction proceed uniformly. After the reaction is completed, cool the obtained mixture to room temperature, centrifuge at 8000 rpm for 10 min to collect the precipitate, discard the supernatant, and wash it with deionized water repeatedly 3 times, with the amount of washing liquid used each time being 80 mL, until the pH value of the washing liquid is stable between 6.5. Dry the obtained precipitate under a vacuum condition of 0.05 MPa for 18 h to obtain reduced graphene oxide.

[0043] The preparation method of the surface-modified Ti3C2T x nanobelts is as follows: Mix 1.0 part of Ti3C2T x nanobelts with 2.0 parts of 1-butyl-3-methylimidazolium tetrafluoroborate in proportion, and then ball-mill them in a planetary ball mill for 60 min. Add the obtained solid to 100 parts of a mixed solution of deionized water and absolute ethanol with a volume ratio of 2:1, and ultrasonically treat it at an ultrasonic power of 200 W for 55 min. After treatment, centrifuge and separate at 12000 rpm for 15 min, discard the supernatant and retain the precipitate. The obtained precipitate is also washed alternately with water and ethanol 3 times and then freeze-dried at -40 °C for 18 h to finally obtain the surface-modified Ti3C2T x nanobelts.

[0044] The preparation method of the Ti3C2T x nanobelts in this example is as follows: First, slowly add 10.0 parts of Ti3AlC2 powder to 100.0 parts of a hydrofluoric acid (HF) solution with a mass concentration of 35%, and magnetically stir at a rate of 200 rpm at 40 °C for 22 h to achieve selective etching of the Al layer in Ti3AlC2 to generate Ti3C2T x precursor solution. After the reaction is completed, centrifuge and separate the mixture at 5000 rpm for 10 min, discard the supernatant and retain the precipitate, wash it with deionized water 4 times, with the amount of washing liquid used each time being 80 mL, until the pH value of the washing liquid is stable between 6.5. The obtained wet precipitate of Ti3C2T x is obtained after freeze-drying for 18 h to obtain Ti3C2T x powder. Subsequently, disperse 2.0 parts of Ti3C2T x powder in 100.0 parts of a potassium hydroxide (KOH) solution with a mass concentration of 5.5 mol / L, and continuously stir and react at 25 °C under nitrogen protection for 20 h, with the stirring rate controlled at 250 rpm. During the reaction process, Ti3C2T xThe lamella is gradually sheared and peeled off along the interlayer direction in an alkaline solution to form a one-dimensional ribbon structure. After the reaction is completed, the system is centrifuged at 5000 rpm for 10 min, the supernatant is discarded, the precipitate is retained and washed with deionized water until the pH value is restored to 6.5, and finally the obtained precipitate is dried under a vacuum condition of 0.05 MPa for 20 h to obtain Ti3C2T x nanoribbon powder.

[0045] The Ti3C2T of this example x nanoribbons have an average width of 50 nm; an average length of 1.5 μm; Ti3C2T x is a two-dimensional carbide with surface terminal groups selected from fluorine (F), hydroxyl (OH) and oxygen (O);

[0046] A preparation method of a flexible antistatic high-temperature-resistant FDC special film in this example includes the following steps:

[0047] S1. Mix the polyimide / graphene precursor solution with surface-modified Ti3C2T x nanoribbons to form a dispersion under mechanical stirring; the stirring rate is 500 rpm, the stirring time is 40 min, and the ambient temperature is 25 °C;

[0048] S2. Heat the dispersion and add 3-aminopropyltriethoxysilane for functionalization treatment; the mixed solution is heated to 80 °C, the dropping rate of 3-aminopropyltriethoxysilane is 0.1 mL / min, the stirring rate is 400 rpm, the reaction time is 60 min, and the reaction is carried out under nitrogen protection;

[0049] S3. Add 2,2'-dihydroxydiphenyl ether, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and diisononyl phthalate for isothermal blending; the isothermal stirring temperature is 80 °C and the time is 30 min;

[0050] S4. Filter and defoam and then coat into a film; the precursor solution is filtered through a 0.45 μm polytetrafluoroethylene filter membrane, the vacuum defoaming pressure is -0.08 MPa, the defoaming time is 20 min, the coating thickness is 50 μm, the film scraping rate is 3 mm / s, the pre-drying temperature is 80 °C and the time is 30 min;

[0051] S5. Gradually increase the temperature, hot press and cure and then cool to obtain the finished product; the hot press heating rate is 3 °C / min, the heat treatment temperature is 250 °C, the heat preservation time is 1.5 h, the cooling rate is 1 °C / min, and the whole process is carried out under a nitrogen atmosphere.

[0052] Figure 1 Shows the Ti3C2T prepared in Example 1 of the present invention xThe morphological characteristics of the nanoribbons can be observed from the figure, showing a typical one-dimensional ribbon structure with a distinct layered stacking morphology and a high aspect ratio. The edges are relatively clear, indicating that the material has been effectively exfoliated, and a ribbon-like MXene structure has been successfully obtained from the precursor. Figure 2 This is the XRD phase analysis diagram of the nanoribbons, further verifying the sufficiency of the etching reaction and the high purity of Ti3C2T x in the product. Therefore, combining the morphological and phase analysis results, it can be confirmed that the present invention has successfully prepared Ti3C2T x nanoribbons with a complete structure, expanded interlayer spacing, and good crystallinity by optimizing the etching and exfoliation processes.

[0053] Example 2

[0054] A flexible antistatic and high-temperature-resistant FDC special film comprises the following raw materials in parts by weight: 75 parts of polyimide / graphene precursor solution, 4.2 parts of surface-modified Ti3C2T x nanoribbons, 0.7 part of 3-aminopropyltriethoxysilane, 0.8 part of 2,2'-dihydroxydiphenyl ether, 0.8 part of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and 1.6 parts of diisononyl phthalate.

[0055] The surface-modified Ti3C2T x nanoribbons are obtained by surface modification of Ti3C2T x nanoribbons with 1-butyl-3-methylimidazolium tetrafluoroborate;

[0056] The preparation method of the polyimide / graphene precursor solution in this example is as follows: Add 3.1 parts of reduced graphene oxide to 5 parts of N-methylpyrrolidone, and disperse it by ultrasonic for 35 min to fully disperse the reduced graphene oxide sheets at the molecular scale to form a uniform and stable graphene dispersion; Add 9.6 parts of 4,4'-diaminodiphenyl ether to the above graphene dispersion, stir and dissolve it under nitrogen protection and at a stirring rate of 330 rpm, and then cool the system to 2 °C; Slowly add 13.6 parts of 4,4'-diphenyl ether dianhydride to the above low-temperature solution in batches. During the reaction, nitrogen protection is continuously maintained, the stirring rate is kept at 330 rpm, the temperature of the reaction system is controlled at 2 °C, and the gradual addition time is controlled at 2.8 h. After the dianhydride is completely dissolved, continue to react at a constant stirring rate for 6 h to obtain a polyamic acid precursor solution containing graphene, that is, a polyimide / graphene precursor solution.

[0057] The preparation method of reduced graphene oxide in this example is as follows: Disperse 9.9 parts of graphene oxide in 86.0 parts of deionized water, stir at a stirring rate of 460 rpm for 35 min. After forming a homogeneous dispersion, slowly add 2.6 parts of vitamin C reducing agent, control the pH value of the system between 4.6, and then heat and react at 85 °C for 99 min. During the reaction process, continuously stir to make the reduction reaction proceed uniformly. After the reaction is completed, cool the obtained mixed solution to room temperature, centrifuge at 8600 rpm for 12 min to collect the precipitate, discard the supernatant, and wash it repeatedly with deionized water 4 times, with the amount of each washing solution being 92 mL, until the pH value of the washing solution is stable between 6.8. Dry the obtained precipitate under a vacuum condition of 0.06 MPa for 20 h to obtain reduced graphene oxide.

[0058] The preparation method of surface-modified Ti3C2T x nanoribbons is as follows: Mix 1.2 parts of Ti3C2T x nanoribbons and 2.3 parts of 1-butyl-3-methylimidazolium tetrafluoroborate in proportion, and then ball-mill them in a planetary ball mill for 63 min. Add the obtained solid to 106 parts of a mixed solution of deionized water and absolute ethanol with a volume ratio of 2:1, and ultrasonically treat it at an ultrasonic power of 230 W for 58 min. After treatment, centrifuge and separate at 12900 rpm for 17 min, discard the supernatant, and retain the precipitate. The obtained precipitate is also washed alternately with water and ethanol 3 times and then freeze-dried at -43 °C for 20 h to finally obtain surface-modified Ti3C2T x nanoribbons.

[0059] The preparation method of Ti3C2T x nanoribbons in this example is as follows: First, slowly add 11.5 parts of Ti3AlC2 powder to 100.0 parts of hydrofluoric acid (HF) solution with a mass concentration of 38%, and magnetically stir at a rate of 230 rpm at 42 °C for 23 h to achieve selective etching of the Al layer in Ti3AlC2 to generate Ti3C2T x precursor solution. After the reaction is completed, centrifuge and separate the mixed solution at 5300 rpm for 12 min, discard the supernatant, and retain the precipitate. Wash it with deionized water 5 times, with the amount of each washing solution being 92 mL, until the pH value of the washing solution is stable between 6.8. The obtained wet precipitate of Ti3C2T x is obtained after freeze-drying for 20 h to obtain Ti3C2T x powder. Subsequently, disperse 2.3 parts of Ti3C2T x powder in 100.0 parts of potassium hydroxide (KOH) solution with a mass concentration of 5.8 mol / L, and continuously stir and react at 27 °C under nitrogen protection for 23 h, with the stirring rate controlled at 280 rpm. During the reaction process, Ti3C2T xThe flakes are gradually sheared and peeled off along the interlayer direction in an alkaline solution to form a one-dimensional ribbon structure. After the reaction is completed, the system is centrifuged at 5300 rpm for 12 min, the supernatant is discarded, the precipitate is retained and washed with deionized water until the pH value is restored to 6.8. Finally, the obtained precipitate is dried under a vacuum condition of 0.06 MPa for 21 h to obtain Ti3C2T x nanoribbon powder.

[0060] The Ti3C2T x nanoribbons in this example have an average width of 80 nm; an average length of 2.1 μm; Ti3C2T x is a two-dimensional carbide with surface terminal groups selected from fluorine (F), hydroxyl (OH) and oxygen (O);

[0061] A method for preparing a flexible anti-static and high-temperature-resistant FDC special film in this example includes the following steps:

[0062] S1. Mix the polyimide / graphene precursor solution with the surface-modified Ti3C2T x nanoribbons to form a dispersion under mechanical stirring; the stirring rate is 560 rpm, the stirring time is 46 min, and the ambient temperature is 27 °C;

[0063] S2. Heat the dispersion and add 3-aminopropyltriethoxysilane for functionalization treatment; the mixed solution is heated to 83 °C, the dropping rate of 3-aminopropyltriethoxysilane is 0.2 mL / min, the stirring rate is 460 rpm, the reaction time is 69 min, and the reaction is carried out under nitrogen protection;

[0064] S3. Add 2,2'-dihydroxydiphenyl ether, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and diisononyl phthalate for constant-temperature co-blending; the constant-temperature stirring temperature is 83 °C and the time is 35 min;

[0065] S4. Filter and defoam, and then coat to form a film; the precursor solution is filtered through a 0.45 μm polytetrafluoroethylene filter membrane, the vacuum defoaming pressure is -0.09 MPa, the defoaming time is 23 min, the coating thickness is 59 μm, the film scraping rate is 4 mm / s, the pre-drying temperature is 86 °C, and the time is 39 min;

[0066] S5. Gradually increase the temperature, hot press and cure, and then cool to obtain the finished product; the hot press heating rate is 4 °C / min, the heat treatment temperature is 265 °C, the heat preservation time is 1.8 h, the cooling rate is 1.3 °C / min, and the whole process is carried out under a nitrogen atmosphere.

[0067] Example 3

[0068] A flexible anti-static and high-temperature resistant FDC special film, comprising the following raw materials in parts by weight: 79 parts of polyimide / graphene precursor solution, surface-modified Ti3C2T x nanoribbons 5.4 parts, 3-aminopropyltriethoxysilane 0.8 parts, 2,2'-dihydroxydiphenyl ether 1.1 parts, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide 1.1 parts, diisononyl phthalate 2.2 parts.

[0069] The surface-modified Ti3C2T x nanoribbons are Ti3C2T x nanoribbons obtained by surface modification with 1-butyl-3-methylimidazolium tetrafluoroborate;

[0070] The preparation method of the polyimide / graphene precursor solution in this example is as follows: Add 3.7 parts of reduced graphene oxide to 6 parts of N-methylpyrrolidone, and disperse it ultrasonically for 39 min to fully disperse the reduced graphene oxide sheets at the molecular scale to form a uniform and stable graphene dispersion; Add 10.2 parts of 4,4'-diaminodiphenyl ether to the above graphene dispersion, stir and dissolve it under nitrogen protection and at a stirring rate of 360 rpm, and then cool the system to 3 °C; Slowly add 14.2 parts of 4,4'-diphenylether dianhydride to the above low-temperature solution in batches. During the reaction, continue nitrogen protection, maintain the stirring rate at 360 rpm, control the reaction system temperature at 3 °C, and control the gradual addition time at 3.1 h. After the dianhydride is completely dissolved, continue to react at a constant stirring rate for 6 h to obtain a graphene-containing polyamic acid precursor solution, that is, a polyimide / graphene precursor solution.

[0071] The preparation method of the reduced graphene oxide in this example is: Disperse 10.8 parts of graphene oxide in 92.0 parts of deionized water, stir at a stirring rate of 520 rpm for 39 min. After forming a uniform dispersion, slowly add 3.2 parts of vitamin C reducing agent, control the pH value of the system between 5.2, and then heat and react at 89 °C for 108 min. During the reaction, continuously stir to make the reduction reaction proceed evenly. After the reaction is completed, cool the obtained mixture to room temperature, centrifuge at 9200 rpm for 13 min to collect the precipitate, discard the supernatant, and wash it repeatedly with deionized water 4 times, with the amount of washing liquid used each time being 104 mL, until the pH value of the washing liquid is stable between 7.1. Dry the obtained precipitate under a vacuum of 0.07 MPa for 22 h to obtain reduced graphene oxide.

[0072] The preparation method of the surface-modified Ti3C2T x nanoribbons in this example is: Add 1.3 parts of Ti3C2T xThe nanobelts are mixed with 2.6 parts of 1-butyl-3-methylimidazolium tetrafluoroborate in proportion and ball-milled in a planetary ball mill for 66 min. The obtained solid is added to 112 parts of a mixed solution of deionized water and absolute ethanol with a volume ratio of 2:1, and ultrasonicated for 61 min under the condition of an ultrasonic power of 260 W. After treatment, it is centrifuged at 13,800 rpm for 18 min, the supernatant is discarded, and the precipitate is retained. The obtained precipitate is washed alternately with water and ethanol 4 times and then freeze-dried at -46 °C for 22 h, and finally surface-modified Ti3C2T x nanobelts are obtained.

[0073] The preparation method of the Ti3C2T x nanobelts in this example is as follows: First, 13.0 parts of Ti3AlC2 powder are slowly added to 100.0 parts of a hydrofluoric acid (HF) solution with a mass concentration of 41%, and magnetically stirred at a rate of 260 rpm at 43 °C for 24 h to achieve selective etching of the Al layer in Ti3AlC2 to generate Ti3C2T x precursor solution. After the reaction is completed, the mixture is centrifuged at 5600 rpm for 13 min, the supernatant is discarded, and the precipitate is retained. It is washed 5 times with deionized water, and the amount of each washing solution is 104 mL until the pH value of the washing solution is stable between 7.1. The obtained Ti3C2T x wet precipitate is obtained as Ti3C2T x powder after freeze-drying for 21 h. Subsequently, 2.6 parts of Ti3C2T x powder is dispersed in 100.0 parts of a potassium hydroxide (KOH) solution with a mass concentration of 6.1 mol / L, and continuously stirred and reacted at 28 °C under nitrogen protection for 26 h, and the stirring rate is controlled at 310 rpm. During the reaction, the Ti3C2T x lamellae are gradually sheared and peeled along the interlayer direction in the alkaline solution to form a one-dimensional banded structure. After the reaction is completed, the system is centrifuged at 5600 rpm for 13 min, the supernatant is discarded, and the precipitate is retained and washed with deionized water until the pH value is restored to 7.1. Finally, the obtained precipitate is dried under a vacuum condition of 0.07 MPa for 22 h to obtain Ti3C2T x nanobelt powder.

[0074] The average width of the Ti3C2T x nanobelts in this example is 110 nm; the average length is 2.7 μm; Ti3C2T x is a two-dimensional carbide with surface terminal groups selected from fluorine (F), hydroxyl (OH), and oxygen (O);

[0075] The preparation method of a flexible antistatic and high-temperature-resistant FDC special film in this example includes the following steps:

[0076] S1. Mix the polyimide / graphene precursor solution with surface-modified Ti3C2T x nanoribbons to form a dispersion under mechanical stirring; the stirring rate is 620 rpm, the stirring time is 52 min, and the ambient temperature is 28 °C;

[0077] S2. Heat the dispersion and add 3-aminopropyltriethoxysilane for functionalization; heat the mixture to 86 °C, the dropping rate of 3-aminopropyltriethoxysilane is 0.2 mL / min, the stirring rate is 520 rpm, the reaction time is 78 min, and the reaction is carried out under nitrogen protection;

[0078] S3. Add 2,2'-dihydroxydiphenyl ether, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and diisononyl phthalate for isothermal blending; the isothermal stirring temperature is 86 °C and the time is 39 min;

[0079] S4. Filter and defoam, then coat to form a film; the precursor solution is filtered through a 0.45 μm polytetrafluoroethylene membrane, the vacuum defoaming pressure is -0.09 MPa, the defoaming time is 26 min, the coating thickness is 68 μm, the film scraping rate is 4 mm / s, the pre-drying temperature is 92 °C, and the time is 48 min;

[0080] S5. Gradually increase the temperature, hot press and cure, and then cool to obtain the finished product; the heating rate of hot pressing is 4 °C / min, the heat treatment temperature is 280 °C, the heat preservation time is 2.1 h, the cooling rate is 1.6 °C / min, and the whole process is carried out under a nitrogen atmosphere.

[0081] Example 4

[0082] A flexible antistatic and high-temperature-resistant FDC special film, comprising the following raw materials in parts by weight: 85 parts of polyimide / graphene precursor solution, surface-modified Ti3C2T x nanoribbons 7.0 parts, 3-aminopropyltriethoxysilane 1.0 part, 2,2'-dihydroxydiphenyl ether 1.5 parts, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide 1.5 parts, diisononyl phthalate 3.0 parts.

[0083] The surface-modified Ti3C2T x nanoribbons are obtained by surface modification of Ti3C2T x nanoribbons with 1-butyl-3-methylimidazolium tetrafluoroborate;

[0084] The preparation method of the polyimide / graphene precursor solution in this example is as follows: Add 4.5 parts of reduced graphene oxide to 8 parts of N-methylpyrrolidone, and disperse it by ultrasonic for 45 minutes to fully disperse the reduced graphene oxide sheets at the molecular scale, forming a uniform and stable graphene dispersion; Add 11.0 parts of 4,4'-diaminodiphenyl ether to the above graphene dispersion, stir and dissolve it under nitrogen protection at a stirring rate of 400 rpm, and then cool the system to 5 °C; Slowly add 15.0 parts of 4,4'-diphenyl ether dianhydride to the above low-temperature solution in batches. During the reaction, continuous nitrogen protection is maintained, the stirring rate is kept at 400 rpm, the temperature of the reaction system is controlled at 5 °C, and the stepwise addition time is controlled within 3.5 h. After the dianhydride is completely dissolved, continue to react for 7 h at a constant stirring rate to obtain a polyamic acid precursor solution containing graphene, that is, a polyimide / graphene precursor solution.

[0085] The preparation method of the reduced graphene oxide in this example is: Disperse 12.0 parts of graphene oxide in 100.0 parts of deionized water, stir at a stirring rate of 600 rpm for 45 minutes. After forming a uniform dispersion, slowly add 4.0 parts of vitamin C reducing agent, control the pH value of the system between 6.0, and then heat and react at 95 °C for 120 minutes. During the reaction process, continuous stirring is carried out to make the reduction reaction proceed evenly. After the reaction is completed, cool the obtained mixture to room temperature, centrifuge at 10000 rpm for 15 minutes to collect the precipitate, discard the supernatant, and wash it repeatedly with deionized water 5 times, with the amount of each washing solution being 120 mL, until the pH value of the washing solution is stable between 7.5. Dry the obtained precipitate under a vacuum condition of 0.08 MPa for 24 h to obtain reduced graphene oxide.

[0086] The preparation method of the surface-modified Ti3C2T x nanoribbons in this example is: Mix 1.5 parts of Ti3C2T x nanoribbons with 3.0 parts of 1-butyl-3-methylimidazolium tetrafluoroborate in proportion and ball-mill them in a planetary ball mill for 70 minutes. Add the obtained solid to 120 parts of a mixed solution of deionized water and absolute ethanol with a volume ratio of 2:1, and ultrasonically treat it under an ultrasonic power of 300 W for 65 minutes. After treatment, centrifuge and separate at 15000 rpm for 20 minutes, discard the supernatant and retain the precipitate. The obtained precipitate is also washed alternately with water and ethanol 4 times and then freeze-dried at -50 °C for 24 h to finally obtain surface-modified Ti3C2T x nanoribbons.

[0087] The Ti3C2T in this example xThe preparation method of the nanoribbon is as follows: First, take 15.0 parts of Ti3AlC2 powder and slowly add it to 100.0 parts of a hydrofluoric acid (HF) solution with a mass concentration of 45%. Under the condition of 45 °C, the magnetic stirring rate is 300 rpm and the reaction lasts for 26 h to achieve the selective etching of the Al layer in Ti3AlC2 to generate Ti3C2T x precursor solution. After the reaction is completed, the mixture is centrifuged at 6000 rpm for 15 min, the supernatant is discarded and the precipitate is retained. It is washed 6 times with deionized water, and the amount of washing liquid used each time is 120 mL until the pH value of the washing liquid is stabilized between 7.5. The obtained Ti3C2T x wet precipitate is freeze-dried for 24 h to obtain Ti3C2T x powder. Subsequently, 3.0 parts of Ti3C2T x powder is dispersed in 100.0 parts of a potassium hydroxide (KOH) solution with a mass concentration of 6.5 mol / L. Under nitrogen protection, the mixture is continuously stirred and reacted at 30 °C for 30 h, and the stirring rate is controlled at 350 rpm. During the reaction, the Ti3C2T x lamellae are gradually sheared and peeled along the interlayer direction in the alkaline solution to form a one-dimensional ribbon structure. After the reaction is completed, the system is centrifuged at 6000 rpm for 15 min, the supernatant is discarded, the precipitate is retained and washed with deionized water until the pH value is restored to 7.5. Finally, the obtained precipitate is dried under a vacuum condition of 0.08 MPa for 24 h to obtain Ti3C2T x nanoribbon powder.

[0088] The average width of the Ti3C2T x nanoribbon in this example is 150 nm; the average length is 3.5 μm; Ti3C2T x is a two-dimensional carbide with surface terminal groups selected from fluorine (F), hydroxyl (OH) and oxygen (O);

[0089] The preparation method of a flexible antistatic high-temperature-resistant FDC special film in this example includes the following steps:

[0090] S1. Mix the polyimide / graphene precursor solution with the surface-modified Ti3C2T x nanoribbon to form a dispersion under mechanical stirring; the stirring rate is 700 rpm, the stirring time is 60 min, and the ambient temperature is 30 °C;

[0091] S2. Heat the dispersion and add 3-aminopropyltriethoxysilane for functionalization treatment; the mixture is heated to 90 °C, the dropping rate of 3-aminopropyltriethoxysilane is 0.3 mL / min, the stirring rate is 600 rpm, the reaction time is 90 min, and the reaction is carried out under nitrogen protection;

[0092] S3. Add 2,2'-dihydroxydiphenyl ether, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and diisononyl phthalate for isothermal blending; the isothermal stirring temperature is 90 °C and the time is 45 min;

[0093] S4. Filter and defoam, then coat to form a film; the precursor solution is filtered through a 0.45 μm polytetrafluoroethylene membrane, the vacuum defoaming pressure is -0.1 MPa, the defoaming time is 30 min, the coating thickness is 80 μm, the film scraping rate is 5 mm / s, the pre-drying temperature is 100 °C, and the time is 60 min;

[0094] S5. Gradually increase the temperature, hot press and cure, and then cool to obtain the finished product; the heating rate of the hot press is 5 °C / min, the heat treatment temperature is 300 °C, the heat preservation time is 2.5 h, the cooling rate is 2 °C / min, and the whole process is carried out under a nitrogen atmosphere.

[0095] Comparative Example 1

[0096] It is basically the same as Example 1, except that the amount of the polyimide / graphene precursor solution is adjusted to 60 parts, resulting in a decrease in the flexibility of the film material and poor electrical conductivity uniformity.

[0097] Comparative Example 2

[0098] It is basically the same as Example 1, except that the amount of surface-modified Ti3C2T x nanoribbons is 1.5 parts, the construction of the conductive network is insufficient, and the electrostatic performance deteriorates significantly.

[0099] Comparative Example 3

[0100] It is basically the same as Example 1, except that 3-aminopropyltriethoxysilane is not added, the interfacial bonding force is poor, and the peel strength of the film material decreases.

[0101] Comparative Example 4

[0102] It is basically the same as Example 1, except that 2,2'-dihydroxydiphenyl ether is not added, the thermal stability decreases significantly, and obvious thermal decomposition occurs.

[0103] Comparative Example 5

[0104] It is basically the same as Example 1, except that 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide is not added, the conductivity of the film material decreases, and the electrostatic dissipation rate slows down.

[0105] Comparative Example 6

[0106] It is basically the same as Example 1, except that diisononyl phthalate is not added, the film material is significantly brittle,

[0107] and the flexibility performance cannot meet the requirements of the bending test.

[0108] Comparative Example 7

[0109] It is basically the same as Example 1, except that the ultrasonic dispersion time of graphene is 10 min, the sheet layer peeling is incomplete, and the composite system is not uniform.

[0110] Comparative Example 8

[0111] It is basically the same as Example 1, except that Ti3C2T x The nanoribbons were not modified with ionic liquid, and agglomerated severely in the polymer matrix, resulting in poor conductive stability.

[0112] Comparative Example 9

[0113] It is basically the same as Example 1, except that the etching temperature of Ti3AlC2 is 60 °C, and the reaction is violent to generate impurities, affecting the purity and sheet structure of Ti3C2T. x Purity and sheet structure.

[0114] Comparative Example 10

[0115] It is basically the same as Example 1, except that the KOH shear peeling time is only 5 h, and the ribbon structure of Ti3C2T is not fully formed, with insufficient interfacial synergy. x Ribbon structure was not fully formed, and the interfacial synergy was insufficient.

[0116] Comparative Example 11

[0117] It is basically the same as Example 1, except that the heating rate during hot pressing is 10 °C / min, resulting in high internal stress in the film material, an incompact structure, and easy cracking.

[0118] Comparative Example 12

[0119] It is basically the same as Example 1, except that the addition amount of diisononyl phthalate in step S3 is 5.0 parts (exceeding the scope of the claim), and the elongation at break of the film is improved.

[0120] Comparative Example 13

[0121] It is basically the same as Example 1, except that the addition amount of 2,2'-dihydroxydiphenyl ether in step S3 is 0.1 part (lower than the scope of the claim), and the thermal decomposition temperature of the film is reduced.

[0122] Performance test:

[0123] Surface Resistance Test (Anti-static Performance): To evaluate the anti-static ability of the FDC film, its surface resistance was tested using the standard method ASTM D257. A high-resistance meter (such as Keithley 6517B) was used to measure the surface resistance of the film material under constant temperature (23 ± 2 °C) and relative humidity (50 ± 5%). The test voltage was set to 100 V. The film material was cut into 10×10 cm square samples and clamped between standard electrodes to measure its surface resistivity.

[0124] Thermal Stability Test (High Temperature Resistance Performance): Using a thermogravimetric analyzer (TGA, such as Thermo TGA Q500, etc.), the thermal decomposition behavior of the FDC film in a nitrogen atmosphere was analyzed according to the ASTM E1131 standard. Approximately 5 - 10 mg of the sample was taken, and its thermogravimetric curve was tested in the temperature range from room temperature to 800 °C at a heating rate of 10 °C / min. Parameters such as the initial decomposition temperature (T5%) and the temperature of the maximum weight loss rate (Tmax) were recorded to evaluate the thermal stability of the material.

[0125] Tensile Property Test (Flexibility and Mechanical Properties): According to the ASTM D882 standard, an electronic universal material testing machine (such as Instron 3365) was used to test the tensile properties of the film material. The sample was cut into rectangular strips with a width of 10 mm and a length of 100 mm, and its breaking strength and elongation at break were measured at a tensile rate of 50 mm / min to reflect its flexibility and mechanical strength, and to compare the structural optimization effects of composite films under different component ratios.

[0126] Flexible Fatigue Cycle Test: Referring to Method B in ISO 7854 standard, a flexible bending fatigue test was carried out. The film material was repeatedly bent 1000 times at a specified radius (such as 5 mm), and whether cracks appeared on its surface and whether its electrical conductivity decreased were observed. Combined with SEM scanning, microscopic cracks were observed to evaluate its reliable durability in actual flexible electronic applications.

[0127] The performances of the special films in Examples 1 - 4 and Comparative Examples 1 - 13 were summarized in Table 1.

[0128] Table 1 Summary of the Performances of the Special Films in Examples 1 - 4 and Comparative Examples 1 - 13

[0129]

[0130] As can be seen from Table 1, the change in the amount of polyimide / graphene precursor solution will significantly affect the flexibility and conductive uniformity of the composite film. A low precursor content will lead to insufficient matrix network, decreased flexibility, and uneven distribution of graphene, resulting in discontinuous conductive channels and thus an increase in surface resistance. Surface-modified Ti3C2T xThe addition amount of the nanobelts directly determines the construction efficiency of the conductive network. Insufficient addition amount will lead to sparse conductive paths, weak current-carrying capacity, resulting in a decline in the electrostatic dissipation performance and a significant increase in the surface resistance. The introduction of 3-aminopropyltriethoxysilane can effectively improve the interfacial bonding force between the inorganic nanobelts and the polymer matrix. In the absence of it, the risk of interfacial peeling will increase, the mechanical strength will decline, and cracks are likely to occur after flexural fatigue. As a heat stabilizer, the absence of 2,2'-dihydroxydiphenyl ether will reduce the thermal decomposition temperature of the polymer system, leading to premature weight loss in the thermogravimetric curve, a decline in thermal stability, and the material is prone to thermal decomposition during high-temperature use. As an ionic liquid, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide can improve the ionic conductivity of the system and the stability of the conductive network. In the absence of it, the electron mobility will decline, the charge dissipation rate will slow down, and the risk of electrostatic accumulation will increase. As a flexible regulator, the absence of diisononyl phthalate will make the material brittle, the elongation at break will decline, the flexural fatigue performance will decrease, and cracks are likely to appear during repeated bending; however, if the addition amount is too high, it may lead to a decline in the mechanical strength of the material, and even softening or surface deformation may occur. Insufficient ultrasonic dispersion time of graphene will cause incomplete exfoliation of the sheets, graphene agglomeration, resulting in non-uniformity inside the composite system, and both the conductivity and mechanical properties will decline. Ti3C2T x If the nanobelts are not modified with ionic liquid, they are prone to agglomeration in the matrix, destroying the continuity and stability of the conductive network, resulting in large fluctuations in conductivity and having a negative impact on the electrostatic dissipation performance. Too high etching temperature of Ti3AlC2 will trigger the generation of side reaction products, affecting the structural integrity and purity of Ti3C2T x and thus reducing its functional performance in the membrane, resulting in a decline in conductivity and thermal stability. Insufficient KOH shear exfoliation time will lead to incomplete formation of the ribbon structure of Ti3C2T x , the sheet dimensions are not ideal, the interfacial synergistic effect is weakened, affecting the overall performance. Too fast heating rate during hot pressing will generate internal stress during the curing process, resulting in an incompact structure of the membrane material, forming microcracks or wrinkles, reducing the flexural fatigue performance and mechanical strength. Although excessive use of the flexible additive can improve the elongation at break and bending performance, it may also cause the surface of the material to be sticky and the structure to be loose, affecting the dimensional stability. Insufficient amount of heat stabilizer will cause premature decomposition of the membrane material or a decrease in the thermogravimetric residue rate in a high-temperature environment, limiting its high-temperature application performance. The above factors interact with each other and jointly determine the key performance manifestations of the FDC special membrane, such as conductivity, thermal stability, flexibility, and structural integrity.

[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them. Although the present invention has been described in detail with reference to the above embodiments, those of ordinary skill in the art should understand that: Any equivalent structural transformation made under the concept of the present invention using the content of the specification and drawings of the present invention should be covered within the protection scope of the claims of the present invention.

Claims

1. A flexible anti-static and high-temperature resistant FDC special film, characterized in that, Comprising the following raw materials in parts by weight: 70-85 parts of polyimide / graphene precursor solution, x 3.0-7.0 parts of surface-modified Ti3C2T nanobelts, 0.5-1.0 part of 3-aminopropyltriethoxysilane, 0.5-1.5 parts of 2,2'-dihydroxydiphenyl ether, 0.5-1.5 parts of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1.0-3.0 parts of diisononyl phthalate. The surface-modified Ti3C2T x nanoribbons are Ti3C2T x nanoribbons obtained by surface modification with 1-butyl-3-methylimidazolium tetrafluoroborate.

2. The flexible anti-static and high-temperature resistant FDC special film according to claim 1, wherein, The preparation method of the polyimide / graphene precursor solution is as follows: Add 2.5 - 4.5 parts of reduced graphene oxide to 3 - 8 parts of N-methylpyrrolidone, and disperse it by ultrasonic for 30 - 45 min to fully disperse the reduced graphene oxide sheets at the molecular scale, forming a uniform and stable graphene dispersion; add 9.0 - 11.0 parts of 4,4'-diaminodiphenyl ether to the above graphene dispersion, stir and dissolve it under nitrogen protection at a stirring rate of 300 - 400 rpm, and then cool the system to 0 - 5 °C; add 13.0 - 15.0 parts of 4,4'-diphenyl ether dianhydride to the above low-temperature solution in batches slowly. During the reaction, keep nitrogen protection, maintain the stirring rate at 300 - 400 rpm, control the reaction system temperature at 0 - 5 °C, and control the gradual addition time at 2.5 - 3.5 h. After the dianhydride is completely dissolved, continue to react for 5 - 7 h at a constant stirring rate to obtain a polyamic acid precursor solution containing graphene, that is, a polyimide / graphene precursor solution.

3. The flexible anti-static and high-temperature resistant FDC special film according to claim 2, characterized in that, The preparation method of the reduced graphene oxide is: Disperse 9.0 - 12.0 parts of graphene oxide in 80.0 - 100.0 parts of deionized water, stir at a stirring rate of 400 - 600 rpm for 30 - 45 min. After forming a uniform dispersion, slowly add 2.0 - 4.0 parts of vitamin C reducing agent, control the pH value of the system between 4.0 - 6.0, and then heat and react at 80 - 95 °C for 90 - 120 min. During the reaction, keep stirring to make the reduction reaction proceed evenly. After the reaction is completed, cool the obtained mixture to room temperature, centrifuge at 8000 - 10000 rpm for 10 - 15 min to collect the precipitate, discard the supernatant, and wash it repeatedly with deionized water for 3 - 5 times, with the amount of each washing solution being 80 - 120 mL, until the pH value of the washing solution is stable between 6.5 - 7.

5. Dry the obtained precipitate under a vacuum condition of 0.05 - 0.08 MPa for 18 - 24 h to obtain reduced graphene oxide.

4. A flexible anti-static and high-temperature resistant FDC special film according to claim 1, wherein, The described surface-modified Ti3C2T x The preparation method of the nanobelts is as follows: Mix 1.0 - 1.5 parts of Ti3C2T x nanobelts with 2.0 - 3.0 parts of 1-butyl-3-methylimidazolium tetrafluoroborate in proportion, and then ball-mill them in a planetary ball mill for 60 - 70 min. Add the obtained solid to 100 - 120 parts of a mixed solution of deionized water and absolute ethanol with a volume ratio of 2:1, and perform ultrasonic treatment for 55 - 65 min under the condition that the ultrasonic power is 200 - 300 W. After treatment, centrifuge at 12000 - 15000 rpm for 15 - 20 min, discard the supernatant and retain the precipitate. The obtained precipitate is also washed alternately with water and ethanol for 3 - 4 times, and then freeze-dried at -40 - -50 °C for 18 - 24 h to finally obtain the surface-modified Ti3C2T x nanobelts.

5. The flexible anti-static and high-temperature resistant FDC special film according to claim 4, wherein, The described Ti3C2T x The preparation method of the nanobelts is as follows: First, take 10.0 - 15.0 parts of Ti3AlC2 powder and slowly add it to 100.0 parts of hydrofluoric acid (HF) solution with a mass concentration of 35% - 45%. Under the condition of 40 - 45 °C, the magnetic stirring rate is 200 - 300 rpm and the reaction lasts for 22 - 26 h to achieve the selective etching of the Al layer in Ti3AlC2 to generate Ti3C2T x precursor solution. After the reaction is completed, the mixture is centrifuged at 5000 - 6000 rpm for 10 - 15 min, the supernatant is discarded and the precipitate is retained. It is washed 4 - 6 times with deionized water, and the amount of washing solution used each time is 80 - 120 mL until the pH value of the washing solution is stable between 6.5 - 7.

5. The obtained Ti3C2T x wet precipitate is freeze-dried for 18 - 24 h to obtain Ti3C2T x powder. Subsequently, 2.0 - 3.0 parts of Ti3C2T x powder is dispersed in 100.0 parts of potassium hydroxide (KOH) solution with a mass concentration of 5.5 - 6.5 mol / L. Under nitrogen protection, the reaction is continuously stirred at 25 - 30 °C for 20 - 30 h, and the stirring rate is controlled at 250 - 350 rpm. During the reaction, the Ti3C2T x lamellae are gradually sheared and peeled along the interlayer direction in the alkaline solution to form a one-dimensional ribbon structure. After the reaction is completed, the system is centrifuged at 5000 - 6000 rpm for 10 - 15 min, the supernatant is discarded, the precipitate is retained and washed with deionized water until the pH value returns to 6.5 - 7.

5. Finally, the obtained precipitate is dried under a vacuum condition of 0.05 - 0.08 MPa for 20 - 24 h to obtain Ti3C2T x nanobelt powder.

6. The flexible anti-static and high-temperature resistant FDC special film according to claim 1, characterized in that, The average width of the Ti3C2T x nanoribbons is 50 to 150 nm; the average length is 1.5 to 3.5 μm.

7. A flexible anti-static and high-temperature resistant FDC special film as claimed in claim 1, wherein, The described Ti3C2T x is a two-dimensional carbide with surface terminal groups selected from fluorine (F), hydroxyl (OH), and oxygen (O).

8. The preparation method of a flexible anti-static and high-temperature resistant FDC special film according to claim 1, characterized in that, It includes the following steps: S1. Mix the polyimide / graphene precursor solution with surface-modified Ti3C2T x nanoribbons to form a dispersion under mechanical stirring; S2. Heat the dispersion and add 3-aminopropyltriethoxysilane dropwise for functionalization treatment; S3. Add 2,2'-dihydroxydiphenyl ether, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and diisononyl phthalate for constant-temperature blending; S4. Filter, defoam, and then coat to form a film; S5. Gradually increase the temperature, hot-press and cure, and then cool to obtain the finished product.

9. The preparation method of a flexible anti-static and high-temperature resistant FDC special film according to claim 8, wherein, The whole process of steps S1 to S5 is carried out under a nitrogen protection atmosphere; In step S1, the stirring rate is 500 - 700 rpm, the stirring time is 40 - 60 min, and the ambient temperature is 25 - 30 °C; In step S2, the mixture is heated to 80 - 90 °C, the dropping rate of 3-aminopropyltriethoxysilane is 0.1 - 0.3 mL / min, the stirring rate is 400 - 600 rpm, the reaction time is 60 - 90 min, and the reaction is carried out under nitrogen protection; In step S3, the constant-temperature stirring temperature is 80 - 90 °C, and the time is 30 - 45 min; In step S4, the precursor solution is filtered through a 0.45 μm polytetrafluoroethylene filter membrane, the vacuum degassing pressure is -0.08 to -0.1 MPa, and the degassing time is 20 to 30 min; the coating thickness is 50 to 80 μm, the film scraping rate is 3 to 5 mm / s, the pre-drying temperature is 80 to 100 °C, and the time is 30 to 60 min.

10. The preparation method of a flexible anti-static and high-temperature resistant FDC special film as described in claim 8, characterized in that, In step S5, the heating rate during hot pressing is 3 to 5 °C / min, the heat treatment temperature is 250 to 300 °C, the holding time is 1.5 to 2.5 h, the cooling rate is 1 to 2 °C / min, and the whole process is carried out under a nitrogen atmosphere.

Citation Information

Patent Citations

  • Anti-static film and preparation method thereof

    CN112239550A

  • MXene / polyimide nanofiber aerogel and preparation method and application thereof

    CN113088078A

  • MXenes polyvinyl alcohol polyimide composite film and preparation method thereof

    CN113736257A

  • Preparation method of biomass boron nitride nanosheet modified polyimide aerogel

    CN114395163A

  • Preparation method of aerogel with electromagnetic shielding and sound absorption functions

    CN114920978A